A rare BMP15 genetic variant in a patient with premature ovarian insufficiency and two spontaneous pregnancies - R. Robeva; S. Andonova; M. Glushkova; T. Todorov; A. Elenkova; A. Savov; S. Zacharieva; A. Todorova (IMR Press, 2020)
Introduction: Premature ovarian insufficiency (POI) is characterized by an unusually early depletion of the ovarian follicular pool in women. Genetic progress in recent years has allowed the identification of different genes that can predispose to the development of POI. Bone morphogenetic protein 15 (BMP15) genetic variants have been associated with diminished ovarian reserve and subfertility in animals and humans. Materials and Methods: Herein, the authors present a 34-year-old Caucasian woman with normal pubertal development, one uncomplicated pregnancy and two spontaneous pregnancies after POI diagnosis. Results: A very rare variant c.269T>C (p.Ile90Thr) in exon 1 of the BMP15 gene was detected. Conclusions: The proper differentiation between genetic variants associated with premature ovarian ageing and mutations that can attribute to irreversible early gonadal impairments is an important task of future studies.